THE FACTORS RELATED TO COMPLIANCE WITH THE CONSUMPTION OF BLOOD SUPPLEMENT AT SENIOR HIGH SCHOOL IN LAHAT REGENCY - Nurhayani, Delvi; Maksuk, Maksuk; Minarti, Minarti (Indonesia Epidemiological Journal, 2024)
Background : Consuming blood supplement tablets is an effort to prevent anemia in young women. The research aims to analyze the compliance of young women in consuming blood supplement tablets. Methods : This research was conducted at high schools in Lahat district in 2023. The calculated sample size was 192 respondents. Data was collected through interviews using questionnaires and analyzed using univariate, bivariate and multivariate methods. Results : The results of the chi - square test obtained variables that were related to compliance with the consumption of blood supplement tablets in young women, namely knowledge, attitudes, exposure to information and availability of iron tablets. Meanwhile, the most dominant factors influencing adolescent girls' compliance in consuming blood supplement tablets are knowledge (pv=0.0005), attitudes (pv=0.005), information exposure (pv=0.043), and availability of iron tablets (pv=0.005). Conclusion : Compliance with consuming blood supplement tablets in young women is related to knowledge, attitudes, exposure to information and availability of iron tablets.